Understanding agile: a case study in educational complexity - Barker, Stephen G. (The International Academic Forum (IAFOR), 2023)
As the nature of engineering concepts, products and processes becomes more intricate and detailed, so the task of understanding, managing and implementing them becomes more complex. This paper takes one such development concept, Agile, and examines how the orthogonal, multi-faceted nature of both the concept and its application makes it difficult to understand and employ and considers in this context the andragogical difficulties posed when trying to teach it to level 7 students. The practice of Agile is often considered to be either the application of methods such as Scrum, extreme programming (XP) or Scaled Agile Framework (SAFe), or the implementation of agile values or principles. In practice, however, a greater level of complexity exists and many more facets need to be considered, such as organisational structure, suitability of project and product, skill set of individuals, and even the mind set of those involved, because the adoption of agile requires more than the use of a technique as part of normal business procedures. In order to understand the complexity of a concept such as agile and the implications which it poses for andragogical teaching and learning strategies, the nature of the concept is first considered to identify the challenges that it creates for education, before a mapping of teaching strategies to agile facets is produced, and thought is given to the creation of an andragogical mechanism which will promote and engender student understanding of the concept and how it can be applied across a range of topic areas in context.
Keywords: Agile; Agility; Andragogy